ANALISIS FAKTOR-FAKTOR PERNIKAHAN DINI DI KABUPATEN PONOROGO - Fitriani, Linda (Inspiratif Pendidikan, 2020)
The phenomenon of early marriage in Ponorogo Regency has increased from time to time. Early marriage is not an ordinary marriage because the perpetrators marry under the age set in Law No. 1 of 1974 concerning marriage. This study aims to determine the factors behind the occurrence of early marriage in Ponorogo Regency. The method used in writing this article is literature study, by analyzing various relevant research works. These factors include education factors, family or parent factors, environmental factors, community and customs, economic factors and accidents or pregnancy outside of marriage. The most influencing factor for early marriage in Ponorogo Regency is pregnancy outside of marriage or 95%.